2012
DOI: 10.1002/jmri.23556
|View full text |Cite
|
Sign up to set email alerts
|

4D flow MRI

Abstract: Traditionally, magnetic resonance imaging (MRI) of flow using phase contrast (PC) methods is accomplished using methods that resolve single‐directional flow in two spatial dimensions (2D) of an individual slice. More recently, three‐dimensional (3D) spatial encoding combined with three‐directional velocity‐encoded phase contrast MRI (here termed 4D flow MRI) has drawn increased attention. 4D flow MRI offers the ability to measure and to visualize the temporal evolution of complex blood flow patterns within an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
237
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(240 citation statements)
references
References 0 publications
2
237
0
1
Order By: Relevance
“…The 4D flow MRI has been widely used in cardiovascular systems to assess dynamic characteristics of blood flow. 17 It offers a variety of parameters that may assist characterization of the blood hemodynamics. Although the validity of the 4D flow technique has been demonstrated through comparison with established techniques such as 2D PC MRI and ultrasound, as well as in experimental setup, the reproducibility and reliability of this technique still need investigation with large cohorts to support its widespread clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4D flow MRI has been widely used in cardiovascular systems to assess dynamic characteristics of blood flow. 17 It offers a variety of parameters that may assist characterization of the blood hemodynamics. Although the validity of the 4D flow technique has been demonstrated through comparison with established techniques such as 2D PC MRI and ultrasound, as well as in experimental setup, the reproducibility and reliability of this technique still need investigation with large cohorts to support its widespread clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the development of fast imaging strategies, the 3D time-resolved phase-contrast MRI with velocity-encoding along three axes (termed 4D flow MRI) technique has become clinically feasible. 17,18 In addition to assessment of the flow velocity, the 4D flow MRI technique allows for the evaluation of several additional hemodynamic parameters that may be derived from the velocity information, such as wall shear stress (WSS), 6,19 blood pressure difference, 20 turbulence kinetic energy, 21 and viscous energy loss, 22 etc. Previous studies have demonstrated clinical applications of this technique for improved characterization of hemodynamics in neurovascular systems, 1,23,24 intraheart and great vessels, 25 and peripheral vessels.…”
mentioning
confidence: 99%
“…Currently, the most common approaches for streamline and pathline visualization for 4D-PC data rely on some form of vessel segmentation for streamline visualization. 26 Such segmentations can be timeconsuming to perform, especially for smaller vessels. Rather than rely on anatomic segmentation to enable streamline rendering, we propose the reverse in this work-that interactive streamline rendering can instead guide delineation and connectivity of small pulmonary veins.…”
Section: Discussionmentioning
confidence: 99%
“…While RPD is most often evaluated clinically using doppler echocardiography, 3D-PCMRI is gaining increasing popularity since it permits quantification of complex blood flow patterns in large vessels and the heart. 7 Moreover, recent work has demonstrated that incorporating the spatial variation not typically observed in standard echo images can have a significant impact on the pressure estimates. 8 3D-PCMRI allows measurement of the velocity field with spatial and temporal resolutions typically ranging from 1.5 to 3 mm 3 and 20 to 40 ms, respectively, and noise levels of around 15% of the maximal velocity.…”
Section: Introductionmentioning
confidence: 99%